Associations of Intellectual Ability with Emotional Intelligence, Academic Achievement and Aggression of Adolescents - Mehwish Mursaleen; Seema Munaf (Journal of Basic & Applied Sciences, 2016)
Purpose: The current study examined the relationship of intellectual ability with emotional intelligence, academic achievement, and aggression of adolescents. Methods: Correlational design was utilized to study the relationship between these variables. Adolescent students (N=500, 50% boys & 50% girls, with the mean age of 15.01 years & SD of 1.11) were approached from different private schools and colleges of Karachi. To measure their intellectual ability, emotional intelligence, and aggression, Draw-A-Person Intellectual Ability Test for children, adolescents, and adults (DAP: IQ), Wong and Law Emotional Intelligence Scale (WLEIS), and Aggression Questionnaire-Short Form (AQ-12) were administered. Their academic achievement was assessed through their percentage of most recent examination. Pearson product moment correlation coefficient was utilized to analyse the results. Results: Intellectual ability was significantly positively related with emotional intelligence and its domains i.e. Self-Emotional Appraisal, Others’ Emotional Appraisal, Use of Emotions, and Regulation of Emotions (p <.01). Intellectual ability and emotional intelligence were also significantly positively related to academic achievement (r=.181, p < .01 & r = .143, p < .01 respectively). Further, intellectual ability and emotional intelligence were significantly negatively related with aggression (r = -.108, p < .01 & r = -.102, p < .05 respectively). Conclusion: Intellectual ability and Emotional intelligence are related constructs which are not only positively related with each other but also with academic achievement while negatively related to the aggression of adolescents. Hence, these two domains of intelligence are equally important in academic achievement as well as in control/expression of aggression.